2011
DOI: 10.1007/s00125-011-2065-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss and exercise on insulin resistance, and intramyocellular triacylglycerol, diacylglycerol and ceramide

Abstract: Aims/hypothesis Intramyocellular lipids, including diacylglycerol (DAG) and ceramides, have been linked to insulin resistance. This randomised repeated-measures study examined the effects of diet-induced weight loss (DIWL) and aerobic exercise (EX) on insulin sensitivity and intramyocellular triacylglycerol (IMTG), DAG and ceramide. Methods Sixteen overweight to obese adults (BMI 30.6±0.8; 67.2±4.0 years of age) with either impaired fasting glucose, or impaired glucose tolerance completed one of two lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
211
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(242 citation statements)
references
References 39 publications
24
211
5
2
Order By: Relevance
“…In the present study, there was an unexpected differential response of muscle lipid content to exercise training, with PCOS women increasing and non-PCOS women decreasing lipid, while IR decreased in both groups. Another study in overweight and obese adults found that exercise-induced improvements in insulin sensitivity were accompanied by increases in IMCL [34,35]. Meex et al [35] demonstrated a trend to increased IMCL with exercise in male patients with type 2 diabetes, whose IR improved, but, in contrast with the present study, mitochondrial function also improved.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, there was an unexpected differential response of muscle lipid content to exercise training, with PCOS women increasing and non-PCOS women decreasing lipid, while IR decreased in both groups. Another study in overweight and obese adults found that exercise-induced improvements in insulin sensitivity were accompanied by increases in IMCL [34,35]. Meex et al [35] demonstrated a trend to increased IMCL with exercise in male patients with type 2 diabetes, whose IR improved, but, in contrast with the present study, mitochondrial function also improved.…”
Section: Discussioncontrasting
confidence: 69%
“…Avoiding body weight gain, or consuming diets low in saturated fatty acids or fructose from nonfruit sources are a likely means to increase hepatic fatty acid oxidation, inhibit ceramide synthesis, and lower circulating ceramide to improve metabolic health (Dubé et al. 2011; Dekker et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, ceramide synthase 1 has specificity for C18 chain lengths and is primarily expressed in skeletal muscles. Ceramide muscle content has been associated with insulin resistance in both normal individuals and athletes, suggesting that elevated ceramides may be a mechanism by which insulin resistance is also associated with accelerated decline in muscle mass and strength (Amati et al ., 2011; Dube et al ., 2011; Kalyani et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%